Quenching-induced atom-stepped bimetallic sulfide heterointerface catalysts for industrial hydrogen generation - Hua Zhang; Nianpeng Li; Sanshuang Gao; Anran Chen; Qihang Qian; Qingquan Kong; Bao Yu Xia; Guangzhi Hu (eScience)
Developing non-noble metal hydrogen evolution reaction (HER) electrocatalysts with high activity and durability at ampere-level current densities is vital for emerging anion exchange membrane (AEM) water electrolysis, but it remains challenging. Here we present an atom-stepped nickel–cobalt bimetallic sulfide (AS-Ni3S2/Co3S4) heterostructure that exhibits superior HER performance, with ultra-low overpotentials of 28 and 195 ​mV at current densities of 10 and 2000 ​mA ​cm−2, respectively. Experimental analyses and theoretical calculations revealed that the work-function-induced interfacial built-in electric field drives electron transfer from Ni3S2 to Co3S4 via Ni–S–Co interfacial bridging, which effectively accelerates water activation and optimizes hydrogen adsorption and desorption. An AEM electrolyzer using an AS-Ni3S2/Co3S4 heterostructure as the cathode required cell voltages of only 1.71 and 1.79 ​V to reach 1.0 and 2.0 ​A ​cm−2, respectively, and operated stably for 1200 ​h without activity degradation.